Primary cutaneous CD8+ cytotoxic T-cell lymphoma of the face with intraoral involvement, resulting in facial nerve palsy after chemotherapy - Travassos, Daphine Caxias [UNESP]; Silveira, Heitor Albergoni [UNESP]; Silva, Evânio Vilela [UNESP]; Panucci, Beatriz Zamboni Martins; da Silva Filho, Nilson Coelho [UNESP]; Silva, Paula Verona Ragusa [UNESP]; Bufalino, Andreia [UNESP]; León, Jorge Esquiche (Wiley, 2022)
The primary cutaneous (PC) CD8+ T-cell lymphoproliferative disorders (LPDs) comprise clinically and histopathologically heterogeneous entities including mycosis fungoides, lymphomatoid papulosis, hydroa-vacciniforme-like LPD, subcutaneous panniculitis-like T-cell lymphoma (TCL), PC acral CD8+ TCL, PC CD8+ aggressive epidermotropic cytotoxic TCL, and PC peripheral TCL, not otherwise specified (PTCL-NOS). We describe a 33-year-old man who presented with progressive facial swelling and lower lip involvement 1 year ago. Microscopy revealed an atypical small to medium-sized lymphoid proliferation exhibiting perivascular accentuation, adnexotropism, and apoptotic cell debris, without surface epithelium involvement. The tumor cells were positive for CD3, CD8, granzyme B, perforin, MUM1/IRF4, and TCR-BF1. The Ki-67 labeling index was 48%. EBER1/2 was negative. Additional studies confirmed localized disease. The diagnosis favored PC-PTCL-NOS. Two months after completing chemotherapy, right-sided facial nerve palsy was diagnosed. CD8+ T-cell LPDs should be considered in the differential diagnosis when assessing facial swelling with intraoral involvement.